Nutritional Therapy in High Output Enterocutaneus Fistula with Ileum Adhesion Grade III-IV : A Case Report - January, Rima; Agussalim Bukhari; Nurbaya Syam; Nurpudji Astuti Taslim; Suryani As’ad; Haerani Rasyid; A. Yasmin Syauki (Faculty of Medicine, Hasanuddin University., 2024)
Introduction and importance: Enterocutaneus fistula (ECF) is an uncommon connection between the gastrointestinal tract and the skin. Loss of intestinal fluid in ECF patients results in an imbalance of electrolytes. The objectives of nutritional therapy were to fulfill nutrient needs, maintain fluid balance, & promote ECF closure. Presentation of case: A 22-year-old male, was diagnosed with post-adhesiolysis and end colostomy surgery. His oral intake was reduced for one month, and he experienced weight loss. We detected a loss of subcutaneous fat and fistula in the right abdomen region and wasted time on physical examination. Abnormal laboratory findings were leucocytosis, thrombocytosis, imbalance electrolyte, and hypoalbuminemia. Discussion: Nutritional assessment was based on mid-upper arm circumference. Nutritional treatment was provided with a calorie target of 2300 kcal and protein 2g/kg ideal body weight (IBW)/day. On the seventh day of treatment, the patient went through relaparotomy due to high output ECF (2000 ml/d) and ileum adhesion grade 3-4. Following surgery, the patient was on parenteral nutrition for eighteen days. Due to high ECF output, protein intake was increased by 2g/kg IBW/day, and fluid intake was adjusted based on fistula output. The patient received a combination of polymeric formula and whey protein by oral intake and micronutrient supplementation at twice the usual dosage. By the 27th day of treatment, ECF output had decreased to 0 ml/d, and laboratory results showed improvement. Conclusions: Adequate nutrition, fluid, and electrolyte balance through optimal nutritional therapy can improve laboratory values and reduce ECF output in ECF patients